Die Genitalien der paläarktischen Tineiden (Lepidoptera: Tineidae). - Petersen, Günther (Contributions to Entomology = Beiträge zur Entomologie, 1957)
The above publication, representing the second part of the work on the genitalia of palaearctic Tineidae, deals with a group of genera the larvae of which are feeding on lichen. There are described several new genera and species especially from Central- and South-Europe. Nomenclatural Acts austriacella Amsel, 1954 (Agnathosia), syn. n. of Agnathosia propulsatella (Rebel, 1892) amseli Petersen, 1957 (Infurcitinea), spec. n. diasi Amsel, 1957 (Infurcitinea), syn. n. of Infurcitinea atrifasciella (Staudinger, 1870) marcunella (Rebel, 1901) (Infurcitinea), Lectotype described as Tinea marcunella roesslerella (Heyden, 1865) (Infurcitinea), Lectotype described as Tinea roesslerella maculata Petersen, 1957 (Lichenotinea), spec. n. montana Petersen, 1957 (Montetinea), spec. n. aritzoella Amsel, 1938 (Novotinea), syn. n. of Novotinea carbonifera (Walsingham, 1900) flavimaculella Toll, 1942 (Tinea), syn. n. of Agnathosia propulsatella (Rebel, 1892) intricatella Chrétien, 1915 (Tinea), syn. n. of Infurcitinea media (Walsingham, 1907) lunatella Benander, 1939 (Tinea), syn. n. of Infurcitinea marianii (Rebel, 1936) Atinea Amsel, 1954 (Tineidae), syn. n. of Infurcitinea Spuler, 1910 Lichenotinea Petersen, 1957 (Tineidae), gen. n. Lichenovora Petersen, 1957 (Tineidae), gen. n. Microtinea Amsel, 1954 (Tineidae), syn. n. of Infurcitinea Spuler, 1910 Montetinea Petersen, 1957 (Tineidae), gen. n. Obesoceras Petersen, 1957 (Tineidae), gen. n.